Early Childhood Education and Natural Sciences: introduction to scientific investigative - Moraes, Tatiana Schneider Vieira de [UNESP]; Zibordi, Maira Isabel [UNESP] (Univ Nove Julho, 2023)
This exhibition discusses issues related to Initiation to Natural Sciences in Early Childhood Education, affirming the child's right to appropriate the knowledge produced by humanity. The goal of this work is to identify signs of children's engagement with investigative actions and, with this perspective, an Investigative Teaching Sequence was elaborated and applied to children of Early Childhood Education. Qualitative research guided the production of data relating to children's records, which were analysed based on evidence associated with the scientific investigation. The results showed that the actions developed in the Kindergarten contributed to the child's understanding of the terrarium construction process, the use of materials and the observation of phenomena as evidence for the investigation process. These actions are fundamental for the theoretical-scientific instrumentalization of the teacher, intentionally guiding their pedagogical practice, as well as offering real opportunities for the integral development of the child.
Keywords: education; early childhood education; initiation to Natural Science